Characterization of the volatile profile of virgin olive oils of Koroneiki and Cypriot cultivars, and classification according to the variety, geographical region and altitude - Kritioti, Angelina; Paikousis, Lefkios; Drouza, Chryssoula (My University, 2020)
This study aims to the investigation of the effects of the geographical region and the botanical origin of olive oils on the profile of volatile compounds (VCs) isolated from monovarietal virgin olive oils (VOOs) from Cypriot, and Koroneiki varieties cultivated in Cyprus in order to establish, for the first time, promising models for botanical and geographical classification. Sixty-four compounds were determined by HS-SPME, GC/MS for one hundred forty VOOs, and statistical analysis of data was performed using LDA and multivariate/univariate ANOVA. Successful categorization, up to 89.3% for the varieties, and 67.9% regarding the altitude classes were obtained. The results showed new markers for the classification of the VOOs according to variety, such as 1-methoxyhexane, and the group C5 compounds, (E)-2-dodecene+(E)-β-ocimene, 3-(4-methyl-3-pentenyl)furan+(E)-4,8-dimethyl-1,3,7nonatriene, which, along with hexyl acetate, group of esters and hydrocarbons exhibited the highest discriminant power among all volatiles/groups based on the different proportions found in VOOs.
Keywords: Cypriot virgin olive oil; Volatiles; GC-MS; Monovarietal; Chemometrics; Altitude; Classification